UNCOVERING THE LINK BETWEEN STUDENTS’ ATTITUDE TOWARD READING AND THEIR COMPREHENSION ABILITIES - Oktaviana, Anggi Try; Asnita, Roma Nur; Amrina, Rizqy Dwi (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
Reading attitude gives good influence to reading comprehension achievement. This study sought to establish a non-experimental research design and employed a correlational research method. Instruments used in this research were a questionnaire to assess reading attitude and a multiple-choice reading comprehension test. The research population consisted of 426 students. The researchers took 105 students as the sample using a random sampling technique. By using Pearson Product-Moment on SPSS in analyzing the data, the researchers found that the sig-t was 0.114, higher than the significant alpha of 0.05 (sig.t > 0.05). It demonstrates that Ho1 is accepted, or that there is a significant negative correlation between the students' reading attitude and reading comprehension. The researchers also discovered that reading attitude has little impact on the 1.5% reading comprehension achievement at SMA Muhammadiyah 1 Palembang. The remaining 98.5 percent was influenced by various factors. Since students' reading attitudes have a minimal impact on their reading comprehension achievement, educators should explore other influential factors, such as teaching methods, vocabulary knowledge, and critical thinking skills. Future research should consider additional factors, such as cognitive abilities, language proficiency, and learning environments, to gain a more comprehensive understanding of reading comprehension influences.